Centrifugal necrotic keratoacanthoma - Caputo Valentina; Fiorella Santi; Castelli Elena (Wolters Kluwer Medknow Publications, 2007)
Centrifugal necrotic keratoacanthoma is a quite rare variant of keratoacanthoma, with a locally aggressive behavior and no tendency to spontaneous involution. We report a typical case of the nasal-orbital region. Based on its clinical, histological and behavioral picture, centrifugal necrotic keratoacanthoma appears as variant of giant keratoacanthoma and can be regarded as an intermediate form in a spectrum where keratoacanthoma and overt squamous cell carcinoma represent the most benign and the most malignant end, respectively, as also highlighted by analogies between the two lesions recently reported in the field of molecular biology.